2021
DOI: 10.3390/ijerph18115710
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of COVID-19 Infection Control Measures by German Dentists: A Qualitative Study to Identify Enablers and Barriers

Abstract: Objectives: COVID-19 infection control measures have been recommended for dental practices worldwide. This qualitative study explored barriers and enablers for the implementation of these measures in German dental practices. Methods: Semi-structured phone interviews were conducted in November/December 2020 (purposive/snowball sampling). The Theoretical Domains Framework (TDF) and the Capabilities, Opportunities and Motivations influencing Behaviors model (COM-B) were used to guide interviews. Mayring’s content… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Reflective and automatic motivation appeared to mediate the capability and opportunity components, similar to previous research [ 35 , 53 ]. The team identified that the teachers should be convinced of the benefits of IcPAB to motivate them participate in the intervention.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Reflective and automatic motivation appeared to mediate the capability and opportunity components, similar to previous research [ 35 , 53 ]. The team identified that the teachers should be convinced of the benefits of IcPAB to motivate them participate in the intervention.…”
Section: Discussionsupporting
confidence: 87%
“…The occurrence of new themes with each new interview was assessed by allowing the research team to evaluate if a saturation of themes occurred. “Such saturation assessment has been proposed as a way of estimating the sample size for qualitative interviews” [ 35 ]. After the seventh interview data saturation occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Low adoption of procedures to avoid aerosol generation was observed in the present study. Such results corroborate what was found in Germany where the main difficulties for this were insufficient knowledge, guidelines and recommendations, as well as the availability of equipment and high costs of PPE [54]. In Turkey, for instance, 90.6% of participants were concerned about aerosol-generating procedures; however, only 53.3% suspended these procedures [55].…”
Section: Discussionsupporting
confidence: 86%
“…[ 29 ] Relevant policy makers and equipment manufacturers should address these points to increase the implementation of infection control measures against COVID-19 and potential future pandemics. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%